Lung Inflammatory Response to Environmental Dust Exposure in Mice Suggests a Link to Regional Respiratory Disease Risk - Burr AC (Dove Medical Press, 2021)
Abigail C Burr,1,* Jalene V Velazquez,1,* Arzu Ulu,1 Rohan Kamath,1 Sang Yong Kim,1 Amanpreet K Bilg,1 Aileen Najera,1 Iman Sultan,1 Jon K Botthoff,2 Emma Aronson,3 Meera G Nair,1 Tara M Nordgren1 1Division of Biomedical Sciences, University of California Riverside, Riverside, CA, 92521, USA; 2Center for Conservation Biology, University of California Riverside, Riverside, CA, 92521, USA; 3Department of Plant Pathology and Microbiology, University of California Riverside, Riverside, CA, 92521, USA*These authors contributed equally to this workCorrespondence: Tara M NordgrenDivision of Biomedical Sciences, University of California Riverside, 92521 University Avenue, Riverside, CA, 92521, USATel +1 951 827 3148Email tmnordgren@gmail.comPurpose: The Salton Sea, California’s largest lake, is designated as an agricultural drainage reservoir. In recent years, the lake has experienced shrinkage due to reduced water sources, increasing levels of aerosolized dusts in surrounding regions. Communities surrounding the Salton Sea have increased asthma prevalence versus the rest of California; however, a connection between dust inhalation and lung health impacts has not been defined.Methods: We used an established intranasal dust exposure murine model to study the lung inflammatory response following single or repetitive (7-day) exposure to extracts of dusts collected in regions surrounding the Salton Sea (SSDE), complemented with in vitro investigations assessing SSDE impacts on the airway epithelium.Results: In these investigations, single or repetitive SSDE exposure induced significant lung inflammatory cytokine release concomitant with neutrophil influx. Repetitive SSDE exposure led to significant lung eosinophil recruitment and altered expression of genes associated with allergen-mediated immune response, including Clec4e. SSDE treatment of human bronchial epithelial cells (BEAS-2B) induced inflammatory cytokine production at 5- and 24-hours post-treatment. When BEAS-2B were exposed to protease activity-depleted SSDE (PDSSDE) or treated with SSDE in the context of protease-activated receptor-1 and − 2 antagonism, inflammatory cytokine release was decreased. Furthermore, repetitive exposure to PDSSDE led to decreased neutrophil and eosinophilic influx and IL-6 release in mice compared to SSDE-challenged mice.Conclusion: These investigations demonstrate potent lung inflammatory responses and tissue remodeling in response to SSDE, in part due to environmental proteases found within the dusts. These studies provide the first evidence supporting a link between environmental dust exposure, protease-mediated immune activation, and respiratory disease in the Salton Sea region.Keywords: Salton Sea, dust exposure, lung inflammation, asthma, proteases, protease-activated receptors